Processes for engaging and retaining women who are experiencing adversity in longitudinal health services research - Anna Price; Hannah Bryson; Ashlee Smith; Fiona Mensah; Sharon Goldfeld (BMC, 2019)
Abstract Background Women and families experiencing socioeconomic and psychosocial adversity are the least likely to access health care but most likely to benefit. For health services to effectively meet the needs of individuals experiencing adversity, research involving the health services must be truly representative. However, individuals experiencing adversity are typically excluded from or underrepresented in health services research. This paper reports on the implementation of a quality improvement approach designed to support recruitment and retention of pregnant women experiencing adversity in a longitudinal, health services randomized controlled trial ("right@home"). Methods right@home recruited Australian women from 10 public maternity hospitals across the states of Victoria and Tasmania who were experiencing adversity (≥2 risk factors on screening survey). Regular follow-up assessments were conducted by phone or face-to-face to child age 2 years. Research processes were designed taking heed of previous research demonstrating effective strategies for recruiting and retaining minority groups (e.g. piloting the recruitment process; recruiting via the health service providing care to the subgroup; remunerating participants); however, we were concerned that important information was missing. Therefore, once recruitment began, we conducted a continuous evaluation of the research processes, testing and implementing changes to processes or new strategies to maximize recruitment and retention (e.g. using a suite of strategies to maintain contact with families, using flexible data collection methods, obtaining consent for data linkage for future health and education data). Results right@home enrolled a large cohort of women (N = 722) experiencing high levels of adversity according to socioeconomic status and psychosocial risk factors, and achieved excellent retention (83% completion at 2 years). Most strategies appeared to increase recruitment and retention. All required additional time from the research team to develop and test, and some required extra funding, which ranged from minor (e.g. printing) to substantial (e.g. salaries, remuneration). Conclusions By taking a quality improvement approach, supported by sufficient resourcing and flexible research processes, it is possible to recruit and retain a large cohort of women experiencing adversity who are typically missed or lost from longitudinal research.